Mendekatkan Jarak melalui Kompetisi Olahraga di Desa Sawitto Enrekang - Sitonda, Syawal; Galib, Andi Ahmad Chabir; Ismaya, Ismaya; Elihami, Elihami; Yusril S, Muh.; Putri, Amelia Wardani; Amalia, Rizka (LP2M Universitas Muhammadiyah Enrekang, 2024)
This article describes a community service initiative in Sawitto Village, Bungin District, Enrekang Regency. This activity aims to build social integration in Sawitto Village through participation in sports competitions. Apart from that, this activity also aims to increase awareness of the importance of a healthy lifestyle and promote the values ​​of solidarity and togetherness among village residents. Community service teams work closely with local community leaders to plan and execute sports competitions. A variety of sports were chosen to cover the diverse interests and skills among the villagers. A participatory approach is applied in all stages of activities, ensuring that all levels of society are involved in planning and implementation. Sports competitions in Sawitto Village have succeeded in creating stronger social bonds among village residents. Wide participation from various age groups shows success in strengthening social integration at the local level. Apart from that, this activity also succeeded in increasing awareness of the importance of a healthy lifestyle and had a positive impact in promoting unity and cooperation in the Sawitto community